Exploring how different types of yoga change psychological resources and emotional well-being across a single session. (March 2020) - Park, Crystal L.; Finkelstein-Fox, Lucy; Groessl, Erik J.; Elwy, A. Rani; Lee, Sharon Y.
Highlights: To gain a better understanding of how yoga brings about beneficial effects, we examined changes in psychological resources and emotions across a single session of yoga. All five psychological resources (mindfulness, body consciousness, self-transcendence, spiritual peace, and social connectedness) increased from pre-to-post yoga session, and all emotions (positive engagement, revitalization, tranquility and exhaustion) improved. Further, improvements in emotions were associated with improvements in psychological resources. Different styles of yoga were associated with differential improvements in psychological resources and emotions. Abstract: Objectives: Yoga demonstrates beneficial effects in many populations, yet our understanding of how yoga brings about these effects is quite limited. Among the proposed mechanisms of yoga are increasing psychological resources (mindfulness, body consciousness, self-transcendence, spiritual peace, and social connectedness) that may bring about salutary effects on emotional wellbeing. Further, yoga is a complex practice comprising meditation, active and restorative postures, and breathwork; however little is known about how different components may affect mechanisms. We aimed to determine how an acute session of yoga (and its specific components) related to pre- to post- session changes in proposed mechanisms (psychological resources) and whether those changes were associated with positive changes in emotions. Design: 144 regular yoga practitioners completed measures of mindfulness, body consciousness, self-transcendence, social connectedness, spiritual peace, and exercise-induced emotions (positive engagement, revitalization, tranquility, exhaustion) immediately before and after a yoga session (N = 11 sessions, each a different type of yoga). Perceived properties of each yoga session, exercise exertion and engagement with the yoga teacher were assessed immediately following the session. Results: Pre-to post- yoga, levels of positive emotions (engagement, tranquility and revitalization) increased while exhaustion decreased . Further, all psychological resources increased and closely tracked improved emotions. Additionally, aspects of the yoga session correlated with changes in psychological resources (mechanisms) and emotions. Conclusions: Yoga may influence multiple psychological mechanisms that influence emotional well-being. Further, different types of yoga may affect different mechanisms. Results can inform yoga interventions aiming to optimize effects through specific mechanisms such as mindfulness or spirituality.